Burn to shine - Maberry, Jonathan (Maberry, Jonathan. Joe Ledger and Rogue Team International ;, 2025)
"Rogue Team International joins Joe Ledger in a new, tension-filled mission to stop a wave of bioterrorism from devastating the country in the fourth installment of bestselling author Jonathan Maberry's ongoing series. A covert group is infiltrating the world's most secure bio-weapons research sites. All across the country, people are acting as human 'disease bombs' by infecting themselves and walking into public places. And heavily-armed groups of illegal private soldiers are massing for some unknown strike. Joe Ledger and the members of Rogue Team International, still reeling from the devastation and heartbreaking losses of their last mission, are forced into relentless action to try and save the country, if not the entire world. Old enemies are rising and joining forces to hit Joe and his team with one devastating blow after another. What is the end game for all of this madness and terror? Outnumbered, outmaneuvered, and outgunned, Joe Ledger has to find a way back from the fires of grief in order to make a stand between these enemies and millions of potential innocent lives. But Joe has allies, too. His team, the vicious fighters of Arklight, and friends who may or may not be entirely human. A war of darkness and light is coming. Who will stand? Who will fall? And how will anyone ever survive?"--